2014
DOI: 10.1177/0734242x14521682
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Ni and Cd speciation in sewage sludge during composting and co-composting with steel slag

Abstract: Sewage sludge and industrial steel slag (SS) pose threats of serious pollution to the environment. The experiments aimed to improve the stabilizing effects of heavy metal Ni and Cd morphology in composting sludge. The total Ni and Cd species distribution and chemical forms in the compost sewage sludge were investigated with the use of compost and co-compost with SS, including degradation. The carbon/nitrogen ratio of piles was regulated with the use of sawdust prior to batch aerobic composting experiments. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In Figure 1, 28 reports, which studied metals speciation by SEPs in organic fertilizers, are shown. It showed that the Tessier method was the most frequently used method with of the total articles [21,22,[40][41][42][43][44][45][46][47], followed by the modified BCR method with [20,23,30,[47][48][49][50][51]. The modified Tessier method [52][53][54][55] and other methods both acc for 14.29%.…”
Section: Sep Of Heavy Metals Speciations In Organic Fertilizersmentioning
confidence: 99%
“…In Figure 1, 28 reports, which studied metals speciation by SEPs in organic fertilizers, are shown. It showed that the Tessier method was the most frequently used method with of the total articles [21,22,[40][41][42][43][44][45][46][47], followed by the modified BCR method with [20,23,30,[47][48][49][50][51]. The modified Tessier method [52][53][54][55] and other methods both acc for 14.29%.…”
Section: Sep Of Heavy Metals Speciations In Organic Fertilizersmentioning
confidence: 99%
“…The exchangeable state of heavy metals determined by the BCR sequential extraction method mainly referred to the heavy metals that were adsorbed on particle surfaces and combined with carbonate minerals (Lu, 2014). In the composting process, when the pH increased, the activated heavy metal ions can easily combine with OH ions contributing to the formation of stable precipitates (Zeng et al, 2014). The OM decomposition promoted the formation of humus substances during composting (Amir et al, 2005;Liu et al, 2007).…”
Section: Influence Of Ph Temperature and Om Decomposition On The Ir Of Heavy Metalsmentioning
confidence: 99%